A UV optical film material and a preparation method and application thereof

CN122923152APending Publication Date: 2026-10-16WUHAN QIANDIE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610997490.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的在于克服上述技术不足,提供一种UV光学膜材及其制备方法和应用,解决现有技术中在长期使用过程中存在光稳定性差、耐疲劳性不足的技术问题

Benefits of technology

[0016] Compared with the prior art, the beneficial effects of the present invention include: ultraviolet light enters from the outer surface, first passes through the anti-reflection layer and the polarizing layer, and reaches the frosted layer. The spiropyran group-modified polymer in the frosted layer absorbs ultraviolet light (300-400nm) through a photochromic reaction, providing effective ultraviolet shielding protection for the iodine-based polyvinyl alcohol polarizing layer and delaying the degradation of iodine complexes (I5). - Photodegradation significantly extends the lifespan of the polarization layer. In the presence of the frosted layer, the polarization retention rate of the polarization layer is ≥97% after 500 hours of QUV aging. The ordered environment of the polarization layer regulates the photochromic properties of spiropyran. The highly ordered orientation structure of the polyvinyl alcohol molecular chains in the polarization layer promotes the directional alignment of spiropyran molecules through interfacial effects, thereby improving the efficiency of the ring-opening-ring-closing isomerization reaction of spiropyran and significantly enhancing its resistance to photofatigue. Experiments show that, in the presence of the polarization layer, the absorbance retention rate of spiropyran after 100 photochromic cycles is ≥95%. The UV optical film material proposed in this invention exhibits good photostability and excellent fatigue resistance during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122923152A_ABST
    Figure CN122923152A_ABST
Patent Text Reader

Abstract

The application discloses a UV optical film material and a preparation method and application thereof, and belongs to the technical field of electronic display film processing. The UV optical film material comprises, from top to bottom, a gradient refractive index anti-reflection layer, a polarizing layer, a frosted layer and a transparent substrate layer. In addition, the application further provides a preparation method of the UV optical film material, which comprises the following steps: coating UV optical transfer glue on the outer surface of the transparent substrate layer, and forming the frosted layer through UV curing; attaching an iodine-based polyvinyl alcohol oriented polarizing layer to the frosted layer to form the polarizing layer; the iodine-based polyvinyl alcohol oriented polarizing layer is attached to the frosted layer; and a gradient refractive index anti-reflection layer is formed on the surface of the frosted layer. In addition, the application further provides application of the UV optical film material in light diffusion films, polarizing films or electronic display screens. The UV optical film material has good light stability and excellent fatigue resistance during long-term use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic display film processing technology, specifically to a UV optical film material, its preparation method, and its application. Background Technology

[0002] With the development of display technologies such as LCD screens and flexible optoelectronic displays, optical functional films (such as brightness enhancement films, polarizing films, anti-reflective films, and surface protective films) are widely applied to screen surfaces to improve display performance and provide protection. Optical functional films typically use polyethylene terephthalate (PET), polycarbonate (PC), cellulose triacetate (TAC), etc., as transparent substrates, and coat the surface of the transparent substrate with an optical functional layer to form a film material with specific optical functions.

[0003] Ultraviolet (UV) curing coating technology has gradually replaced traditional coating processes due to its advantages such as high-efficiency curing and low energy consumption. However, existing UV optical films still have the following technical problems: Spiropyran-based photochromic compounds added to achieve anti-yellowing properties exhibit poor photostability and insufficient fatigue resistance during long-term use. Spiropyran compounds undergo irreversible degradation after repeated photochromic cycles, a phenomenon known as "photofatigue."

[0004] Traditional iodine-based polarizers typically have a thickness exceeding 200 μm, making it difficult to meet the demands for thinner and lighter display devices. Furthermore, the iodine complex (I5) in the iodine-based polarizing layer... - It is easily decomposed under ultraviolet light and humid heat conditions, which leads to a decrease in polarization degree and affects the long-term stability of the polarization layer.

[0005] Therefore, there is an urgent need to develop a method that can solve the problems of poor light stability and insufficient fatigue resistance during long-term use. Summary of the Invention

[0006] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a UV optical film material, its preparation method and application, thereby solving the technical problems of poor light stability and insufficient fatigue resistance in the long-term use of the prior art.

[0007] To achieve the above-mentioned technical objectives, the present invention provides a UV optical film material, which comprises, from top to bottom, a gradient refractive index antireflective layer, a polarizing layer, a frosted layer, and a transparent substrate layer; the frosted layer is made of UV optical transfer adhesive, the UV optical transfer adhesive contains a spiropyran group modified polymer, and the spiropyran group modified polymer is obtained by copolymerization of polyurethane containing spiropyran groups and UV polyester acrylate.

[0008] In any embodiment, the UV optical transfer adhesive comprises, by weight parts: 20-40 parts of polyurethane containing spiropyran groups, 10-20 parts of UV polyester acrylate, 25-40 parts of UV modified epoxy acrylate, 2-3 parts of free radical initiator, 3-7 parts of photoinitiator, and 10-25 parts of UV monomer.

[0009] In any embodiment, the photoinitiator is one or both of TPO initiator and 1-hydroxycyclohexylphenyl ketone; and / or, the UV monomer is one or more of 1,6-hexanediol diacrylate, acrylamide morpholine, and tetrahydrofuran methyl acrylate; and / or, the free radical initiator is one or both of azobisisobutyronitrile and benzoyl peroxide.

[0010] In any embodiment, the UV optical transfer adhesive is prepared by the following steps: S11. Polyurethane containing spiropyran groups is mixed with UV polyester acrylate and heated to 60-80°C under nitrogen protection. Then, a free radical initiator is added and the mixture is stirred to obtain a spiropyran group modified polymer. S12. The spiropyran-modified polymer obtained in step S12 is stirred and mixed with UV-modified epoxy acrylate, and then a photoinitiator is added at 50-70°C and stirred to obtain a mixed adhesive solution. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution of step S12 and stir to mix. Then, cure at 35-45°C to obtain UV optical transfer adhesive.

[0011] In any embodiment, in step S11, the stirring speed of the added free radical initiator is 300-500 rpm, and the stirring time is 4-8 hours; and / or, in step S12, the stirring speed of the added photoinitiator at 50-70°C is 1500-2500 rpm, and the stirring time is 10-20 minutes; and / or, in step S13, the ripening time is 5-10 hours.

[0012] In any embodiment, the polarizing layer is an iodine-based polyvinyl alcohol oriented polarizing layer; and / or, the transparent substrate layer is a PET film substrate.

[0013] In any embodiment, the thickness of the transparent substrate layer is 100–200 μm, the thickness of the frosted layer is 8–20 μm, and the thickness of the gradient refractive index antireflective layer is 100–300 nm.

[0014] Furthermore, this invention also proposes a method for preparing a UV optical film, comprising the following steps: Step S21: Apply UV optical transfer adhesive to the outer surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: The iodine-based polyvinyl alcohol orientation polarization layer is bonded to the frosted layer to form a polarization layer; the iodine-based polyvinyl alcohol orientation polarization layer is formed by dyeing the polyvinyl alcohol film by immersing it in an iodine-potassium iodide solution, and then bonding it to the frosted layer after uniaxial stretching orientation and boric acid crosslinking curing. Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

[0015] Furthermore, the present invention also proposes the application of the above-mentioned UV optical film material in light diffusion films, polarizing films, or electronic displays.

[0016] Compared with the prior art, the beneficial effects of the present invention include: ultraviolet light enters from the outer surface, first passes through the anti-reflection layer and the polarizing layer, and reaches the frosted layer. The spiropyran group-modified polymer in the frosted layer absorbs ultraviolet light (300-400nm) through a photochromic reaction, providing effective ultraviolet shielding protection for the iodine-based polyvinyl alcohol polarizing layer and delaying the degradation of iodine complexes (I5). - Photodegradation significantly extends the lifespan of the polarization layer. In the presence of the frosted layer, the polarization retention rate of the polarization layer is ≥97% after 500 hours of QUV aging. The ordered environment of the polarization layer regulates the photochromic properties of spiropyran. The highly ordered orientation structure of the polyvinyl alcohol molecular chains in the polarization layer promotes the directional alignment of spiropyran molecules through interfacial effects, thereby improving the efficiency of the ring-opening-ring-closing isomerization reaction of spiropyran and significantly enhancing its resistance to photofatigue. Experiments show that, in the presence of the polarization layer, the absorbance retention rate of spiropyran after 100 photochromic cycles is ≥95%. The UV optical film material proposed in this invention exhibits good photostability and excellent fatigue resistance during long-term use.

[0017] The characteristic absorption of the spiropyran closed-ring state in the 480-600 nm range complements the transmission spectrum of the iodine-based polarization layer, resulting in a transmittance fluctuation of ≤3% in the entire visible light band (400-700 nm) and significantly better optical uniformity than a single polarization layer. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the structure of the UV optical film material of Embodiment 1 of the present invention.

[0019] Explanation of reference numerals in the attached figures: 1. Gradient refractive index antireflective layer; 2. Polarizing layer; 3. Frosted layer; 4. Transparent substrate layer. Detailed Implementation

[0020] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0021] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0022] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0023] This specific embodiment provides a UV optical film material, comprising, from top to bottom, a gradient refractive index antireflective layer, a polarizing layer, a frosted layer, and a transparent substrate layer. The frosted layer is made of UV optical transfer adhesive, which contains a spiropyran-modified polymer. The spiropyran-modified polymer is prepared by copolymerizing polyurethane containing spiropyran groups with UV polyester acrylate. The polarizing layer is an iodine-based polyvinyl alcohol oriented polarizing layer. By introducing spiropyran groups into the polyurethane molecular chain and then copolymerizing it with UV polyester acrylate, the spiropyran groups are covalently anchored to the polymer backbone, fundamentally solving the problems of migration, aggregation, and phase separation of spiropyran compounds in the resin matrix.

[0024] In some embodiments, the UV optical transfer adhesive comprises, by weight parts: 20-40 parts of polyurethane containing spiropyran groups, 10-20 parts of UV polyester acrylate, 25-40 parts of UV modified epoxy acrylate, 2-3 parts of free radical initiator, 3-7 parts of photoinitiator, and 10-25 parts of UV monomer; the photoinitiator is one or both of TPO initiator and 1-hydroxycyclohexylphenyl ketone; the UV monomer is one or more of 1,6-hexanediol diacrylate, acryloylmorpholine, and tetrahydrofuran methyl acrylate; and the free radical initiator is one or both of azobisisobutyronitrile and benzoyl peroxide.

[0025] The UV optical transfer adhesive is prepared by the following steps: S11. Add polyurethane containing spiropyran groups and UV polyester acrylate to a reaction vessel, heat to 60-80°C under nitrogen protection, add a free radical initiator, and stir the reaction at 300-500 rpm for 4-8 hours to obtain a spiropyran group modified polymer. S12. Add the spiropyran-modified polymer and UV-modified epoxy acrylate obtained in step S12 into a reaction vessel and stir for 15-30 min. Add a photoinitiator at 50-70°C and stir for 10-20 min at a speed of 1500-2500 rpm to obtain a mixed adhesive solution. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution in step S12, stir at 800-1000 rpm for 20-30 minutes, transfer to a vacuum filter tank for degassing and filtration, and then cure at 35-45℃ for 5-10 hours to obtain the UV optical transfer adhesive.

[0026] In some embodiments, the polarizing layer is an iodine-based polyvinyl alcohol (PVA) oriented polarizing layer. The iodine-based PVA polarizing layer is created by immersing a PVA film in an iodine-potassium iodide solution, allowing iodine molecules to adsorb onto the PVA molecular chains, and then subjecting it to unidirectional stretching and orientation to align the iodine molecules in an orderly manner along the stretching direction, thereby generating a polarization effect.

[0027] The spiropyran-modified polymer in the frosted layer can absorb ultraviolet light (300-400 nm) and undergo a reversible photochromic reaction from closed-ring spiropyran (SP) to open-ring anthocyanin (MC), thereby consuming ultraviolet light energy, reducing the ultraviolet radiation dose reaching the polarization layer, and delaying the reaction of iodine complexes (I5) in the iodine-based polyvinyl alcohol polarization layer. - Photodegradation of polarization layers extends their lifespan.

[0028] The polyvinyl alcohol molecular chains in the polarization layer are unidirectionally stretched to form a highly ordered orientation structure. This anisotropic environment promotes the directional arrangement of spiropyran molecules in the frosted layer through the interface effect, making the ring-opening-ring-closing isomerization reaction of spiropyran more efficient in a specific direction, thus improving the anti-photofatigue performance of spiropyran. The closed-ring state of spiropyran in the spiropyran group modified polymer has characteristic absorption in the wavelength range of 480-600 nm, which complements the transmission spectrum of the iodine-based polyvinyl alcohol polarization layer, making the transmittance of the film material more uniform in the visible light region.

[0029] In some embodiments, the transparent substrate layer is a PET film substrate with a thickness of 100–200 μm; the frosted layer has a thickness of 8–20 μm; and the gradient refractive index antireflective layer has a thickness of 100–300 nm.

[0030] In some embodiments, the gradient refractive index antireflective layer is composed of nanoporous titanium dioxide with a refractive index gradient from 1.8 to 2.3. A gradient refractive index structure is formed on the surface of the polarization layer using a sol-gel method or magnetron sputtering to achieve a wide-band antireflective effect.

[0031] This specific embodiment also proposes a method for preparing a UV optical film, including the following steps: Step S21: Apply UV optical transfer adhesive to the outer surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: The iodine-based polyvinyl alcohol orientation polarization layer is bonded to the frosted layer to form a polarization layer; the iodine-based polyvinyl alcohol orientation polarization layer is formed by dyeing the polyvinyl alcohol film by immersing it in an iodine-potassium iodide solution, and then bonding it to the frosted layer after uniaxial stretching orientation and boric acid crosslinking curing. Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

[0032] Furthermore, this specific embodiment also proposes the application of the above-mentioned UV optical film material in light diffusion films, polarizing films, or electronic displays.

[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0034] In this invention, the terms "some embodiments," "this embodiment," and examples are used to describe a subset of all possible embodiments. However, it is understood that "some embodiments" can be the same subset or different subsets of all possible embodiments and can be combined with each other without conflict.

[0035] If the application documents contain similar descriptions such as "first / second", the following explanation shall be added: In the following description, the terms "first / second / third" are used only to distinguish similar objects and do not represent a specific ordering of objects. It is understood that "first / second / third" may be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.

[0036] In this embodiment, the term "and / or" is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, object A and / or object B can represent three situations: object A exists alone, object A and object B exist simultaneously, and object B exists alone.

[0037] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0038] The preparation of the iodine-based polyvinyl alcohol orientation polarization layer (i.e., iodine-based PVA polarization layer) in the following examples includes: S21. Preparation of coating solution: Dissolve polyvinyl alcohol (PVA) powder in deionized water to prepare a PVA aqueous solution with a mass concentration of 10%. Heat to 95°C and stir to dissolve for 2 hours. Filter to remove bubbles to obtain PVA solution.

[0039] S22, Iodine-based staining solution: Add iodine (I2) and potassium iodide (KI) to the above PVA solution. The mass concentration of I2 is 1.0%, and the mass ratio of KI to I2 is 10:1 (so that I2 is converted to I3). - I5 - The solution is prepared in polyiodide ion form and boric acid (H3BO3) is added as a crosslinking agent precursor, with the amount of boric acid added being 3% of the mass of PVA. The mixture is stirred thoroughly, and the pH is adjusted to 4 with dilute hydrochloric acid, maintaining the solution temperature at 25°C.

[0040] S23. Coating and Stretching: The above dyeing solution is evenly coated onto the surface of the frosted layer. After coating, it enters the first drying oven: temperature 70℃, wind speed 2m / s, drying time 3 minutes, reducing the moisture content of the PVA film to 15%. The dried PVA film is preheated at 670℃ for 40 seconds to enhance the activity of the PVA molecular chain segments. In the stretching zone at 75℃, uniaxial longitudinal stretching is performed at a stretching ratio of 4.5 times (stretching direction is the machine direction), with the stretching speed controlled at 1 times / second. During the stretching process, the PVA molecular chains are highly oriented along the stretching direction, and the iodide ion complexes are oriented along the molecular chains to form a dichroic absorption axis. Tension is maintained at the end of the stretching, and heat-set at 85℃ for 40 seconds, partially crystallizing and fixing the oriented structure.

[0041] S24. Boric Acid Crosslinking and Fixation Treatment: Prepare an aqueous solution containing 5% boric acid (H3BO3) and 10% potassium iodide (KI). Spray the crosslinking solution onto the stretched PVA film at 50°C. Boric acid undergoes esterification and crosslinking with the hydroxyl groups of PVA, forming a three-dimensional network, which improves the water resistance and dimensional stability of the PVA film. After crosslinking, dry in a 90°C oven for 2 minutes to reduce the film moisture content to below 5%. During this process, excess potassium iodide and boric acid form a protective layer, inhibiting iodide ion migration.

[0042] In the following embodiments or comparative examples, magnetron sputtering is used to deposit a gradient refractive index antireflective layer on the polarization layer. During the deposition process, the flow rate of the reactive gas is gradually changed so that the refractive index gradually changes from 1.70 to 1.30. The magnetron sputtering uses a Si target, the oxygen flow rate is linearly increased from 5 sccm to 30 sccm, and the working pressure is 0.8 Pa. The SiO2 aerogel particles on the surface of the transition layer act as induced nucleation sites during the magnetron sputtering process, promoting the formation of a self-organized gradient structure of the gradient refractive index antireflective layer.

[0043] In the following examples or comparative examples, the hydroxyl value of the acrylate in the UV polyester acrylate is 60±5 mg KOH / g; and the epoxy equivalent of the UV modified epoxy acrylate is 500 g / mol.

[0044] Example 1

[0045] This embodiment proposes a UV optical film material, combined with... Figure 1 From top to bottom, it includes a gradient refractive index antireflective layer 1, an iodine-based polyvinyl alcohol oriented polarization layer 2, a frosted layer 3, and a transparent substrate layer 4; the transparent substrate layer 4 is a PET film substrate with a thickness of 150 μm; the frosted layer 3 has a thickness of 15 μm; the gradient refractive index antireflective layer 1 has a thickness of 200 nm; the frosted layer 3 is made of UV optical transfer adhesive; In this embodiment, the UV optical transfer adhesive, calculated by weight, comprises: 30 parts of polyurethane containing spiropyran groups, 15 parts of UV polyester acrylate, 30 parts of UV-modified epoxy acrylate, 2 parts of free radical initiator azobisisobutyronitrile, 5 parts of photoinitiator TPO initiator, and 15 parts of UV monomer 1,6-hexanediol diacrylate, prepared by the following steps: S11. Polyurethane containing spiropyran groups and UV polyester acrylate are added to a reaction vessel, heated to 70°C under nitrogen protection, and free radical initiator azobisisobutyronitrile is added. The mixture is stirred at 400 rpm for 6 hours to obtain a spiropyran group modified polymer. S12. Add the spiropyran group modified polymer and UV modified epoxy acrylate obtained in step S12 into the reaction vessel and stir for 20 min. Heat to 60℃ and add photoinitiator. Stir for 15 min at a speed of 2000 rpm. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution in step S12, stir at 900 rpm for 25 min, transfer to a vacuum filter tank for degassing and filtration, and then cure at 40°C for 8 hours to obtain the UV optical transfer adhesive.

[0046] This embodiment also proposes a method for preparing a UV optical film, including the following steps: Step S21: Apply UV optical transfer adhesive to the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: Attach the iodine-based polyvinyl alcohol orientation polarization layer onto the frosted layer to form a polarization layer; Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the iodine-based polyvinyl alcohol orientation polarization layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index antireflection layer.

[0047] Example 2

[0048] This embodiment proposes a UV optical film material, which, from top to bottom, comprises a gradient refractive index antireflective layer, an iodine-based polyvinyl alcohol oriented polarization layer, a frosted layer, and a transparent substrate layer; the transparent substrate layer is a PET film substrate with a thickness of 100 μm; the frosted layer has a thickness of 20 μm; the gradient refractive index antireflective layer has a thickness of 300 nm; and the frosted layer is made of UV optical transfer adhesive. In this embodiment, the UV optical transfer adhesive, calculated by weight, comprises: 20 parts of polyurethane containing spiropyran groups, 20 parts of UV polyester acrylate, 40 parts of UV-modified epoxy acrylate, 3 parts of free radical initiator azobisisobutyronitrile, 3 parts of photoinitiator TPO initiator, and 10 parts of UV monomer acryloylmorpholine, and is prepared by the following steps: S11. Polyurethane containing spiropyran groups and UV polyester acrylate are added to a reaction vessel, heated to 60°C under nitrogen protection, and free radical initiator azobisisobutyronitrile is added. The mixture is stirred at 300 rpm for 8 hours to obtain a spiropyran group modified polymer. S12. Add the spiropyran group modified polymer and UV modified epoxy acrylate obtained in step S12 into the reaction vessel and stir for 15 min. Heat to 50°C and add photoinitiator. Stir for 20 min at a speed of 1500 rpm. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution in step S12, stir at 800 rpm for 30 min, transfer to a vacuum filter tank for degassing and filtration, and then cure at 35°C for 10 hours to obtain the UV optical transfer adhesive.

[0049] This embodiment also proposes a method for preparing a UV optical film, including the following steps: Step S21: Apply UV optical transfer adhesive to the surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: Attach the iodine-based polyvinyl alcohol orientation polarization layer onto the frosted layer to form a polarization layer; Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

[0050] Example 3

[0051] This embodiment proposes a UV optical film material, which, from top to bottom, comprises a gradient refractive index antireflective layer, an iodine-based polyvinyl alcohol oriented polarization layer, a frosted layer, and a transparent substrate layer; the transparent substrate layer is a PET film substrate with a thickness of 200 μm; the frosted layer has a thickness of 8 μm; the gradient refractive index antireflective layer has a thickness of 100 nm; and the frosted layer is made of UV optical transfer adhesive. In this embodiment, the UV optical transfer adhesive, calculated by weight, comprises: 40 parts of polyurethane containing spiropyran groups, 10 parts of UV polyester acrylate, 25 parts of UV-modified epoxy acrylate, 2 parts of free radical initiator benzoyl peroxide, 7 parts of photoinitiator 1-hydroxycyclohexylphenyl ketone, and 25 parts of UV monomer tetrahydrofuran methyl acrylate, prepared by the following steps: S11. Polyurethane containing spiropyran groups and UV polyester acrylate are added to a reaction vessel, heated to 80°C under nitrogen protection, and free radical initiator benzoyl peroxide is added. The mixture is stirred at 500 rpm for 4 hours to obtain a spiropyran group modified polymer. S12. Add the spiropyran-modified polymer and UV-modified epoxy acrylate obtained in step S12 to the reactor and stir for 30 min. Heat to 70°C and add photoinitiator. Stir for 10 min at a speed of 2500 rpm. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution in step S12, stir at 1000 rpm for 20 minutes, transfer to a vacuum filter tank for degassing and filtration, and then cure at 45°C for 5 hours to obtain the UV optical transfer adhesive.

[0052] This embodiment also proposes a method for preparing a UV optical film, including the following steps: Step S21: Apply UV optical transfer adhesive to the surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: Attach the iodine-based polyvinyl alcohol orientation polarization layer onto the frosted layer to form a polarization layer; Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

[0053] Example 4

[0054] This embodiment proposes a UV optical film material, which, from top to bottom, comprises a gradient refractive index antireflective layer, an iodine-based polyvinyl alcohol oriented polarization layer, a frosted layer, and a transparent substrate layer; the transparent substrate layer is a PET film substrate with a thickness of 170 μm; the frosted layer has a thickness of 10 μm; the gradient refractive index antireflective layer has a thickness of 250 nm; and the frosted layer is made of UV optical transfer adhesive. In this embodiment, the UV optical transfer adhesive, calculated by weight, comprises: 35 parts of polyurethane containing spiropyran groups, 16 parts of UV polyester acrylate, 3 parts of free radical initiator azobisisobutyronitrile, 35 parts of UV-modified epoxy acrylate, 4 parts of photoinitiator 1-hydroxycyclohexylphenyl ketone, and 15 parts of UV monomer acryloylmorpholine, and is prepared by the following steps: S11. Polyurethane containing spiropyran groups and UV polyester acrylate are added to a reaction vessel, heated to 70°C under nitrogen protection, and free radical initiator azobisisobutyronitrile is added. The mixture is stirred at 300 rpm for 4 hours to obtain a spiropyran group modified polymer. S12. Add the spiropyran-modified polymer and UV-modified epoxy acrylate obtained in step S12 into a reaction vessel and stir for 20 min. Heat to 65°C and add photoinitiator. Stir for 10 min at a speed of 1500. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution in step S12, stir at 900 rpm for 25 min, transfer to a vacuum filter tank for degassing and filtration, and then cure at 40°C for 5 hours to obtain the UV optical transfer adhesive.

[0055] This embodiment also proposes a method for preparing a UV optical film, including the following steps: Step S21: Apply UV optical transfer adhesive to the surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: Attach the iodine-based polyvinyl alcohol orientation polarization layer onto the frosted layer to form a polarization layer; Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

[0056] Comparative Example 1 This comparative example is a UV optical film material containing only a frosted layer (excluding a polarizing layer).

[0057] This comparative example proposes a UV optical film material, which, from top to bottom, comprises a gradient refractive index antireflective layer, a frosted layer, and a transparent substrate layer; the transparent substrate layer is a PET film substrate with a thickness of 150 μm; the frosted layer has a thickness of 15 μm; the gradient refractive index antireflective layer has a thickness of 200 nm; and the frosted layer is made of UV optical transfer adhesive. In this embodiment, the UV optical transfer adhesive, calculated by weight, comprises: 30 parts of polyurethane containing spiropyran groups, 15 parts of UV polyester acrylate, 30 parts of UV-modified epoxy acrylate, 2 parts of free radical initiator azobisisobutyronitrile, 5 parts of photoinitiator TPO initiator, and 15 parts of UV monomer 1,6-hexanediol diacrylate, prepared by the following steps: S11. Polyurethane containing spiropyran groups and UV polyester acrylate are added to a reaction vessel, heated to 70°C under nitrogen protection, and free radical initiator azobisisobutyronitrile is added. The mixture is stirred at 400 rpm for 6 hours to obtain a spiropyran group modified polymer. S12. Add the spiropyran group modified polymer and UV modified epoxy acrylate obtained in step S12 into the reaction vessel and stir for 20 min. Heat to 60℃ and add photoinitiator. Stir for 15 min at a speed of 2000 rpm. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution in step S12, stir at 900 rpm for 25 min, transfer to a vacuum filter tank for degassing and filtration, and then cure at 40°C for 8 hours to obtain the UV optical transfer adhesive.

[0058] This embodiment also proposes a method for preparing a UV optical film, including the following steps: Step S21: Apply UV optical transfer adhesive to the surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using the sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

[0059] Comparative Example 2 This comparative example is a UV optical film material containing only a polarizing layer (excluding the frosted layer).

[0060] This comparative example proposes a UV optical film material, which, from top to bottom, comprises a gradient refractive index antireflective layer, an iodine-based polyvinyl alcohol oriented polarization layer, and a transparent substrate layer; the transparent substrate layer is a PET film substrate with a thickness of 150 μm; and the gradient refractive index antireflective layer has a thickness of 200 nm.

[0061] This comparative example also proposes a method for preparing a UV optical film, comprising the following steps: Step S21: The iodine-based polyvinyl alcohol orientation polarization layer is bonded to the surface of the transparent substrate layer to form a polarization layer; Step S22: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the polarization layer using the sol-gel method or magnetron sputtering method, serving as a gradient refractive index antireflection layer.

[0062] The UV optical films prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, and the results are shown in Tables 1 and 2.

[0063] It should be noted that the photo-fatigue test method is as follows: the film sample is irradiated with 365nm ultraviolet light until photochromic saturation (open-ring state), and then irradiated with visible light until fading is complete (closed-ring state). The above cycle is repeated 100 times, and the ratio of the maximum absorption peak absorbance of the open-ring state at the 100th cycle to the maximum absorption peak absorbance of the open-ring state at the 1st cycle is measured.

[0064] The polarization efficiency test method is as follows: use a spectrophotometer to test the transmittance T1 and T2 of the polarization layer in the direction parallel to the orientation direction and in the direction perpendicular to the orientation direction, respectively. The polarization efficiency P = (T1-T2) / (T1+T2)×100%.

[0065] Table 1

[0066] This invention copolymerizes polyurethane containing spiropyran groups with UV-cured polyester acrylate, anchoring the spiropyran groups covalently to the polymer chain. This effectively inhibits the photo-fatigue degradation of spiropyran, maintaining an absorbance retention rate of over 94% after 100 cycles. Simultaneously, the spiropyran-modified polymer in the frosted layer provides effective UV shielding protection for the polarization layer, maintaining a polarization retention rate of ≥96% after 500 hours of QUV aging.

[0067] Table 2

[0068] Based on Table 2, the results show that there is a significant synergistic effect between the spiropyran-modified polymer in the frosted layer and the polarization layer. The presence of the polarization layer improves the anti-photofatigue performance of spiropyran, while the presence of the frosted layer improves the UV aging resistance of the polarization layer. The synergistic effect of the two makes the overall optical uniformity of the film material better than that of a simple superposition of a single functional layer.

[0069] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A UV optical film material, characterized in that, From top to bottom, it includes a gradient refractive index antireflective layer, a polarizing layer, a frosted layer, and a transparent substrate layer; the frosted layer is made of UV optical transfer adhesive, which contains a spiropyran group-modified polymer, which is obtained by copolymerization of polyurethane containing spiropyran groups and UV polyester acrylate.

2. The UV optical film material according to claim 1, characterized in that, The UV optical transfer adhesive comprises, by weight, 20-40 parts of polyurethane containing spiropyran groups, 10-20 parts of UV polyester acrylate, 25-40 parts of UV modified epoxy acrylate, 2-3 parts of free radical initiator, 3-7 parts of photoinitiator, and 10-25 parts of UV monomer.

3. The UV optical film material according to claim 2, characterized in that, The photoinitiator is one or both of TPO initiator and 1-hydroxycyclohexylphenyl ketone; and / or, the UV monomer is one or more of 1,6-hexanediol diacrylate, acryloylmorpholine and tetrahydrofuran methyl acrylate; and / or, the free radical initiator is one or both of azobisisobutyronitrile and benzoyl peroxide.

4. The UV optical film material according to claim 2, characterized in that, The UV optical transfer adhesive is prepared by the following steps: S11. Polyurethane containing spiropyran groups is mixed with UV polyester acrylate and heated to 60-80°C under nitrogen protection. Then, a free radical initiator is added and the mixture is stirred to obtain a spiropyran group modified polymer. S12. The spiropyran-modified polymer obtained in step S12 is stirred and mixed with UV-modified epoxy acrylate, and then a photoinitiator is added at 50-70°C and stirred to obtain a mixed adhesive solution. S13. Under nitrogen protection, add the UV monomer to the mixed adhesive solution of step S12 and stir to mix. Then, cure at 35-45°C to obtain UV optical transfer adhesive.

5. The UV optical film material according to claim 4, characterized in that, In step S11, the free radical initiator is added and the stirring speed is 300-500 rpm, and the stirring time is 4-8 hours.

6. The UV optical film material according to claim 4, characterized in that, In step S12, the photoinitiator is added at 50-70°C and the stirring speed is 1500-2500 rpm for 10-20 min; and / or, in step S13, the ripening time is 5-10 hours.

7. The UV optical film material according to claim 1, characterized in that, The polarizing layer is an iodine-based polyvinyl alcohol oriented polarizing layer; and / or, the transparent substrate layer is a PET film substrate.

8. The UV optical film material according to claim 1, characterized in that, The thickness of the transparent substrate layer is 100–200 μm, the thickness of the frosted layer is 8–20 μm, and the thickness of the gradient refractive index antireflective layer is 100–300 nm.

9. A method for preparing a UV optical film material according to any one of claims 1-8, characterized in that, Includes the following steps: Step S21: Apply UV optical transfer adhesive to the outer surface of the transparent substrate layer and cure it with UV to form a frosted layer; Step S22: The iodine-based polyvinyl alcohol orientation polarization layer is bonded to the frosted layer to form a polarization layer; the iodine-based polyvinyl alcohol orientation polarization layer is formed by dyeing the polyvinyl alcohol film by immersing it in an iodine-potassium iodide solution, and then bonding it to the frosted layer after uniaxial stretching orientation and boric acid crosslinking curing. Step S23: A gradient refractive index nanoporous titanium dioxide layer is formed on the surface of the frosted layer using a sol-gel method or magnetron sputtering method, serving as a gradient refractive index anti-reflection layer.

10. The application of the UV optical film material according to any one of claims 1-8 in light diffusion films, polarizing films, or electronic displays.